Ln(x+9)+ln(x-9)=o

Simple and best practice solution for Ln(x+9)+ln(x-9)=o equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for Ln(x+9)+ln(x-9)=o equation:


Simplifying
Ln(x + 9) + ln(x + -9) = o

Reorder the terms:
nL(9 + x) + ln(x + -9) = o
(9 * nL + x * nL) + ln(x + -9) = o
(9nL + nxL) + ln(x + -9) = o

Reorder the terms:
9nL + nxL + ln(-9 + x) = o
9nL + nxL + (-9 * ln + x * ln) = o
9nL + nxL + (-9ln + lnx) = o

Reorder the terms:
-9ln + lnx + 9nL + nxL = o

Solving
-9ln + lnx + 9nL + nxL = o

Solving for variable 'l'.

Move all terms containing l to the left, all other terms to the right.

Add '-9nL' to each side of the equation.
-9ln + lnx + 9nL + -9nL + nxL = -9nL + o

Combine like terms: 9nL + -9nL = 0
-9ln + lnx + 0 + nxL = -9nL + o
-9ln + lnx + nxL = -9nL + o

Add '-1nxL' to each side of the equation.
-9ln + lnx + nxL + -1nxL = -9nL + -1nxL + o

Combine like terms: nxL + -1nxL = 0
-9ln + lnx + 0 = -9nL + -1nxL + o
-9ln + lnx = -9nL + -1nxL + o

Reorder the terms:
-9ln + lnx + 9nL + nxL + -1o = -9nL + 9nL + -1nxL + nxL + o + -1o

Combine like terms: -9nL + 9nL = 0
-9ln + lnx + 9nL + nxL + -1o = 0 + -1nxL + nxL + o + -1o
-9ln + lnx + 9nL + nxL + -1o = -1nxL + nxL + o + -1o

Combine like terms: -1nxL + nxL = 0
-9ln + lnx + 9nL + nxL + -1o = 0 + o + -1o
-9ln + lnx + 9nL + nxL + -1o = o + -1o

Combine like terms: o + -1o = 0
-9ln + lnx + 9nL + nxL + -1o = 0

The solution to this equation could not be determined.

See similar equations:

| 11+2x=-3(x-1)+3x | | w=12+24 | | 2(b+2)-(9+b)=-4 | | -4x-6=-2x-2 | | 20x^2+8x+28=0 | | 6w-21=7 | | w=5-15 | | (x-9)2=-6 | | z/18=-23 | | 3n-6=3 | | ln(3x-9)=21 | | x-4x+7=5x-6x-17 | | 5(3z-1)-5(z+4)=6(z+1) | | -2x+4=-4x-7 | | 5x(2)=29 | | -16-3x=8(-7-x) | | x+(y+19)=153 | | 2(6t+1)-4(t+2)=34 | | x+y+19=153 | | (6n+4)-(12n-9)=2n+29 | | 24a^2-26ab-5b^2= | | 5z+2.9=12.8-4z | | 3x-10x=35 | | -3+(-1)= | | x=05x+x-4 | | 18x+18= | | 4+4(-7)= | | 0.16x+0.8(x-5)=0.01(2x-1) | | 2x^2=-6+8a | | 5(6x-12)=3(20x-10) | | -42m-14=76 | | 7/9=11/x |

Equations solver categories